Pendampingan Penguatan Rohani Berbasis Nilai-Nilai Moderasi - Laila, ST Noer Farida; Ridwan, Muhammad Mahfud; Mutrofin, Mutrofin; Himawati, Widatul; Mukarromah, Khodijatul; Hanifa, Nihla Nadida (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Assistance for spiritual and religious strengthening is an important effort for every human being/individual, especially for those who are inmates in correctional institutions. This mentoring activity aims at moderation values which are expected to have a positive impact on the rehabilitation process of the assisted residents. The aim of this activity is to build awareness and be able to implement the values of moderation in the Trenggalek. Detention center environment. The aim of this service activity is to find out how the understanding and tolerance of the inmates is based on the value of moderation and to find out how the values of moderation are implemented. The implementation method in this servise program uses a research model based on Participatory Action Research (PAR). This method tries to realize three benchmarks, namely the exixtence of a shared commitment with the community and the existence of new institutions in the community that are built based on needs. During the training, various methods are used to ensure active participation and involvement of all participants. The FGD session was held by inviting speakers from several different backgrounds. Group discussions, simulations and role-playing are implemented to help inmates understand the perspectives of othes religions and build empathy. These activities aim to facilitate constructive dialogue and reduce interreligious stereotypes or prejudice. This training was designed with a socio-religious approach to the diversity of religions and beliefs among the inmates. The result of this service is a significant increase in understanding of the values of religious moderation among the inmates.